Verbal comprehension of university students - Piacente, Telma (2012)
This paper presents the preliminary results of a broader research on performance and selfperception in reading and writing of university students. In particular, it focuses on verbal comprehension given its connection with reading comprehension. Reading comprehension is crucial, especially while constructing a situational model—achieved by integrating the information provided in the text with relevant prior knowledge. A random pilot sample of 60 students from third year, male and female, of an average age of 23 was selected. The Vocabulary, Information and Analogies tests from WAIS III were administered. The Verbal Comprehension findings show central tendency scores similar to those of the standardization sample with minor dispersion, with specific cases of scores in the lower average limit. Several comments are given on the performance of university students and other observations regarding the type of mistakes made in the answers provided which deserve further considerations. Preliminary conclusions point to a lack of and/or insufficient information, conceptual confusion with some terms of relatively high frequency and difficulties in the conceptualization process. These preliminary findings deserve further attention due to their impact in successful learning from texts.